Inhibition of Oxidative Stress and Related Signaling Pathways in Neuroprotection - Maja Jazvinšćak Jembrek (Antioxidants)
Oxidative stress, characterized by increased production of reactive oxygen species (ROS) and disturbed redox homeostasis, is one of the key mechanisms underlying synaptic loss and neuronal death in various neurodegenerative diseases [...]